1995
DOI: 10.1136/gut.37.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Cross linking of collagen is increased in colonic diverticulosis.

Abstract: Development of colonic diverticulosis is a function of age and declining colonic wall mechanical strength. The latter is partly a consequence of changes in the collagen structure. Collagen from unaffected human colons (n=20, age range 20-80 years) and those with colonic diverticulosis (n=5, age range 67-80 years) were obtained at necropsy. The total collagen content was measured as the hydroxyproline content and cross linkage by collagen solubility in weak acid was studied. The colonic total collagen content w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
20

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(93 citation statements)
references
References 11 publications
(4 reference statements)
3
67
0
20
Order By: Relevance
“…The viscoelastic properties of elastin and collagen give the colonic wall its stability, strength and maintenance of the shape [15, 16, 34, 35]. Collagen has inter- and intramolecular cross-links that stabilize and give strength to the tissue where it is located, but excessive cross-linking of collagen is believed to lead to rigidity and loss of tensile strength [36]. An autopsy study by Wess et al [36] showed that – although the total amount of collagen was not elevated in diverticular colon compared to controls – differences in collagen nature with increased cross-linking were noted with increasing age and in diverticular colon, which might cause the rigidity and inflexibility of the colonic wall.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The viscoelastic properties of elastin and collagen give the colonic wall its stability, strength and maintenance of the shape [15, 16, 34, 35]. Collagen has inter- and intramolecular cross-links that stabilize and give strength to the tissue where it is located, but excessive cross-linking of collagen is believed to lead to rigidity and loss of tensile strength [36]. An autopsy study by Wess et al [36] showed that – although the total amount of collagen was not elevated in diverticular colon compared to controls – differences in collagen nature with increased cross-linking were noted with increasing age and in diverticular colon, which might cause the rigidity and inflexibility of the colonic wall.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Collagen has inter- and intramolecular cross-links that stabilize and give strength to the tissue where it is located, but excessive cross-linking of collagen is believed to lead to rigidity and loss of tensile strength [36]. An autopsy study by Wess et al [36] showed that – although the total amount of collagen was not elevated in diverticular colon compared to controls – differences in collagen nature with increased cross-linking were noted with increasing age and in diverticular colon, which might cause the rigidity and inflexibility of the colonic wall. Two animal studies from the same group also suggested that fiber content in diet might determine the nature of collagen, and the development of diverticular disease [15, 16].…”
Section: Pathophysiologymentioning
confidence: 99%
“…A possible explanation for this finding is that the elderly might have a declining colonic wall mechanical strength which is partly a consequence of changes in the collagen structure [18]. Perhaps, an increasing number of diverticular diseases in the elderly may contribute to a higher rate of CP because an endoscopist could inadvertently push a scope through a large diverticulum (see Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Aufgrund des Nachweises einer vermehrten Elastineinlagerung in der Längsmuskulatur [28,29,32] wird angenommen, dass es dadurch zu einer Kontraktion der Taenien mit Verkürzung des Darmrohres ("Concertina-Kolon") [29][30][31] [33,34]. In einzelnen Untersuchungen wurde gezeigt, dass der Gesamtkollagengehalt [28,32] sowie die Verknüpfung (cross-linking) der Kollagenfasern bei der Divertikelkrankheit erhöht ist [35]. Es wird vermutet, dass dadurch die Anpassungsfähigkeit des Darmrohres an die wechselnden intraluminalen Drücke herabgesetzt ist.…”
Section: Hintergrundunclassified